Incidence of postoperative flare-ups after single-visit and multiple-visit endodontic therapy in permanent teeth - Anju Singh; Konark; Abhas Kumar; Jazib Nazeer; Rohit Singh; Supriya Singh (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2020)
Aim: Single- and multiple-visit root canal treatment has been the subject of long-standing debate in the endodontic community, so the purpose of this study was to determine the incidence of postoperative flare-up after single- and multiple-visit endodontic therapy in permanent teeth. Materials and Methods: A total of 65 children aged >10 years who underwent root canal treatment were randomly categorized equally into two treatment groups: the first group underwent single-visit treatment, and the other group underwent multiple-visit therapy. The visual analog scale was employed to evaluate pain preoperatively and postoperatively after obturation. Recall visits were carried out after 1 week, 1 and 3, 6 and 9 months. The Statistical Package for the Social Sciences version 15.0 was employed for statistical analysis. Results: Except at the baseline, at all the other time intervals, the mean pain score in the multiple-visit group was higher as compared to that of the single-visit group; statistically no significant difference was found. Conclusion: The mean pain score in the single-visit group was lower as compared to that of the multiple-visit group; however, the difference between the two groups was statistically significant (P > 0.05).